Conceptual paper on Halal and Haram: systems level approach - Butt, Rehan Muzammil; Muflih, Betania Kartika; Jan, Muhammad Tahir; Hassan, Masood; Ali, Muhammad Abid (Reviews Of Management Sciences, Karachi, 2021)
Purpose: